Composition for chemically excited silicon-aluminum material, chemically excited silicon-aluminum material as well as preparation method and application of chemically excited silicon-aluminum material

By using the basic components, carbon black and chemical exciters in the composition for chemically excited silicon-aluminum materials, chemically excited silicon-aluminum materials with high conductivity and high strength, the problems of high cost and insufficient conductivity of existing conductive cement concrete materials are solved, and low-cost and high-performance material applications are realized.

CN119912202AActive Publication Date: 2025-05-02TONGJI UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510092117.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing conductive cement concrete materials are costly and the conductivity needs to be improved in large-scale applications.

Method used

A chemically excited silicon-aluminum material composition, which includes a base component, carbon black and a chemical exciter, is prepared by stirring and mixing and curing treatment to prepare a chemically excited silicon-aluminum material with high conductivity and high strength.

Benefits of technology

The comprehensive optimization of chemically excited silicon-aluminum materials in terms of electrical properties, mechanical properties and costs is achieved, and it has the characteristics of low cost, high conductivity and high strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251865710000111
    Figure BDA0005251865710000111
Patent Text Reader

Abstract

The invention relates to the technical field of chemical excitation silicon-aluminum materials, and discloses a composition for a chemical excitation silicon-aluminum material, the chemical excitation silicon-aluminum material as well as a preparation method and application of the chemical excitation silicon-aluminum material. The composition contains a main agent and an auxiliary agent, the main agent comprises a basic component, carbon black and a chemical activator; on the basis of the total weight of the basic components, the basic components comprise 60-80 wt% of slag, 5-20 wt% of metakaolin and 5-20 wt% of silica fume; the specific surface area of the carbon black is 405-435 m < 2 > / g, and the average particle size is 20-40 nm. The chemically excited silicon-aluminum material obtained by adopting the composition for the chemically excited silicon-aluminum material provided by the invention has excellent mechanical strength and conductivity, and has good application prospects in the fields of building structure health monitoring, traffic state detection, energy conversion and energy storage, snow melting and deicing, building heating and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemically excited silicon-aluminum materials, and in particular to a composition for chemically excited silicon-aluminum materials, chemically excited silicon-aluminum materials, and a preparation method and application thereof. Background Art

[0002] Conductive cement concrete is an advanced functional building material. By adding highly conductive fillers such as carbon fiber, graphene, carbon nanotubes, and carbon black to the matrix material, its electrical properties can be improved, making it more intelligent.

[0003] Currently, cement-based materials are often used as the matrix material of conductive cement concrete, but the production of cement is a high-energy consumption process, accompanied by the emission of a large amount of dust and harmful gases such as sulfur, carbon, and nitrogen, which imposes a heavy burden on the environment.

[0004] Chemically excited aluminosilicate material is a new type of aluminosilicate inorganic gelling material. It uses industrial / agricultural solid waste or natural minerals rich in aluminosilicate as the main raw materials. The activity of the raw materials is stimulated under the action of strong alkali or strong acid, and dissolution-condensation-condensation reactions occur. After the Si-O bonds and Al-O bonds of the aluminosilicate raw materials are broken, active aluminate ions and silicate ions are released. These ions are hydrolyzed (or hydrated) and then re-condensed to form a dimer or polymer structure of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron, which is further condensed and finally hardened into an amorphous or semi-crystalline inorganic gelling material.

[0005] Chemically excited silicon-alumina materials significantly reduce carbon emissions and energy consumption in the preparation process due to their firing-free process and recycling of industrial waste; in addition, the high alkaline ion content and microporous structure inside the chemically excited silicon-alumina materials enable them to exhibit certain ionic conductivity properties.

[0006] In order to make the chemically excited silicon-aluminum material have better conductivity, conductive materials such as graphite, carbon fiber, carbon black, etc. are usually added during the preparation of the chemically excited silicon-aluminum material.

[0007] CN105218004A discloses a method for preparing a conductive geopolymer, comprising the following steps: 1) mixing graphene, dispersant A and water, grinding and dispersing to obtain a preliminarily dispersed graphene dispersion;

[0008] 2) Mixing the alkali metal silicate solution with the graphene dispersion obtained in step 1), stirring evenly, adding dispersant B, grinding and dispersing to obtain a graphene-dispersed alkali-activated solution, wherein the modulus of the alkali metal silicate solution is 1-4 and the solid content is 30-60%; 3) Mixing the silicon-aluminum raw material with granulated blast furnace slag, grinding to obtain a composite geopolymer powder; 4) Mixing the composite geopolymer powder obtained in step 3) with the graphene-dispersed alkali-activated solution obtained in step 2) and stirring evenly to obtain a conductive geopolymer. This prior art not only gives the geopolymer good conductive properties, but also maintains the mechanical properties of the geopolymer; however, the cost required for applying this prior art to large-scale conductive concrete / conductive geopolymer composite material projects is relatively high and the conductive properties still need to be improved. Summary of the invention

[0009] The purpose of the present invention is to provide a chemically excited silicon-aluminum material which has good electrical and mechanical properties and low cost.

[0010] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composition for chemically excited silicon-aluminum materials, wherein the composition contains a main agent and an auxiliary agent; the main agent includes a base component, carbon black and a chemical activator;

[0011] Relative to 100 parts by weight of the base component, the content of the carbon black is 0.5-6 parts by weight, and the content of the chemical stimulant is 40-50 parts by weight;

[0012] Based on the total weight of the basic component, the basic component contains 60-80wt% of slag, 5-20wt% of metakaolin and 5-20wt% of silica fume;

[0013] The specific surface area of ​​the carbon black is 405-435m 2 / g, average particle size is 20-40nm;

[0014] The modulus of the chemical activator is less than 0.8, and the content of alkali metal oxide in the chemical activator is 3-4wt%, and the solid content is 14-25wt%.

[0015] The second aspect of the present invention provides a method for preparing a chemically excited silicon-aluminum conductive material, which is carried out using the components in the chemically excited silicon-aluminum material composition described in the first aspect, comprising:

[0016] (1) Stirring and mixing the components in the main agent and the components in the auxiliary agent to obtain a slurry;

[0017] (2) The slurry is subjected to a curing treatment to obtain the chemically excited silicon-aluminum material.

[0018] The third aspect of the present invention provides a chemically excited silicon-aluminum material prepared by the method described in the second aspect.

[0019] The fourth aspect of the present invention provides the application of the chemically excited silicon-aluminum material described in the third aspect in the field of building materials.

[0020] The chemically excited silicon-aluminum material obtained by using the chemically excited silicon-aluminum material composition provided by the present invention has the advantages of high conductivity, high strength, low carbon environmental protection and low cost, and realizes the structural and functional integration of the chemically excited silicon-aluminum material.

[0021] The method for preparing chemically excited silicon-aluminum materials provided by the invention is simple to operate and is conducive to large-scale production. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] It should be noted that the average particle size in the present invention refers to the particle size corresponding to when the cumulative particle size distribution fraction in the carbon black powder sample reaches 50% when tested by a nanoparticle size analyzer.

[0024] It should be noted that, in the present invention, the modulus of the chemical activator is the ratio of the molar amount of SiO2 to the molar amount of the alkali metal oxide in the chemical activator. Exemplarily, when the chemical activator is a potassium-based activator (K2O·nSiO2), the modulus of the chemical activator is the ratio of the molar amount of SiO2 to the molar amount of K2O.

[0025] It should be noted that the iron oxide in the present invention refers to ferric oxide.

[0026] As mentioned above, the first aspect of the present invention provides a composition for chemically excited silicon-aluminum materials, the composition containing a main agent and an auxiliary agent; the main agent includes a base component, carbon black and a chemical activator;

[0027] Relative to 100 parts by weight of the base component, the content of the carbon black is 0.5-6 parts by weight, and the content of the chemical stimulant is 40-50 parts by weight;

[0028] Based on the total weight of the basic component, the basic component contains 60-80wt% of slag, 5-20wt% of metakaolin and 5-20wt% of silica fume;

[0029] The specific surface area of ​​the carbon black is 405-435m 2 / g, average particle size is 20-40nm;

[0030] The modulus of the chemical activator is less than 0.8, and the content of alkali metal oxide in the chemical activator is 3-4wt%, and the solid content is 14-25wt%.

[0031] The present invention provides examples to illustrate the meaning of the content of alkali metal oxides in the chemical activator in the present invention. For example, when the chemical activator is a sodium-based activator (Na2O·nSiO2), the content of alkali metal oxides in the sodium-based activator is the ratio of the mass of Na2O to the total mass of Na2O and SiO2 in the chemical activator; when the chemical activator is a potassium-based activator (K2O·nSiO2), the content of alkali metal oxides in the potassium-based activator is the ratio of the mass of K2O to the total mass of K2O and SiO2 in the chemical activator.

[0032] Preferably, the modulus of the chemical stimulant is 0.6-0.7. The present invention finds that under this preferred condition, the chemically stimulated silicon-aluminum material obtained has good fluidity and early strength, and can show excellent mechanical properties in a shorter curing time, and still maintains relatively excellent electrical properties at the age of 28 days.

[0033] Preferably, the chemical activator is a potassium-based activator.

[0034] According to a preferred embodiment, the potassium-based activator is prepared by a method comprising the following steps:

[0035] Potassium silicate, potassium hydroxide and water are mixed to obtain a potassium-based activator.

[0036] The present invention has no special requirements for the mixing method, and it is only necessary to make the potassium silicate, potassium hydroxide and water uniformly mixed. Those skilled in the art can select the method according to needs.

[0037] It should be noted that the present invention has no special requirements on the type of water, which can be deionized water or ultrapure water for example, and those skilled in the art can choose according to their needs. The present invention is only described once in one aspect without repeating the description, and those skilled in the art should not understand it as a limitation of the present invention.

[0038] Preferably, the content of the carbon black is 4-6 parts by weight relative to 100 parts by weight of the base component. The inventors of the present invention have found that in this preferred embodiment, the mechanical properties and the conductive properties of the chemically excited silicon-aluminum material can be well balanced.

[0039] Preferably, based on the total weight of the base component, the base component contains 70-80 wt% of slag, 5-15 wt% of metakaolin and 5-15 wt% of silica fume.

[0040] Preferably, the content of SiO2 in the silica ash is ≮96wt%.

[0041] Preferably, the average particle size of the silica fume is 0.35-21.5 μm, and the specific surface area is 1.75×10 5 -1.80×10 5 m 2 / g.

[0042] According to a preferred specific implementation, the content of silicon dioxide in the slag is 30-45wt%, the content of aluminum oxide is 10-20wt%, and the content of calcium oxide is 35-50wt%.

[0043] Preferably, the content of silicon dioxide in the metakaolin is 45-60wt%, the content of aluminum oxide is 35-50wt%, and the content of iron oxide is less than 2wt%.

[0044] Preferably, the auxiliary agent includes a dispersant and a defoamer;

[0045] Relative to 100 parts by weight of the base component, the content of the dispersant is 0.01-6 parts by weight, and the content of the defoaming agent is 0.005-3 parts by weight.

[0046] Preferably, the dispersant is selected from at least one of polyvinyl pyrrolidone, polyacrylic acid salt, polyacrylamide, polyvinylidene fluoride and sodium dodecylbenzene sulfonate.

[0047] Preferably, the defoaming agent is selected from at least one of tributyl phosphate, polydimethylsiloxane, polypropylene glycol and polyoxyethylene.

[0048] As mentioned above, the second aspect of the present invention provides a method for preparing a chemically excited silicon-aluminum material, which is carried out using the components in the composition for chemically excited silicon-aluminum material described in the first aspect, comprising:

[0049] (1) Stirring and mixing the components in the main agent and the components in the auxiliary agent to obtain a slurry;

[0050] (2) The slurry is subjected to a curing treatment to obtain the chemically excited silicon-aluminum material.

[0051] According to a preferred embodiment, in step (1), the step of stirring and mixing the components in the main agent and the components in the auxiliary agent comprises:

[0052] S1: mixing carbon black, an additive and a chemical activator by stirring to obtain a mixed solution I;

[0053] S2: The mixed solution I and the mixed material containing the basic components are subjected to a second stirring and mixing process to obtain a slurry.

[0054] Preferably, in step S1, the first stirring and mixing conditions include: a rotation speed of 500-1000 rpm and a time of 20-60 min.

[0055] Preferably, in step S2, the second stirring and mixing conditions include: a rotation speed of 120-150 rpm and a time of 2-3 min.

[0056] Preferably, in step (2), the curing treatment conditions include: temperature of 15-25° C. and humidity of 60-90%.

[0057] According to a preferred specific implementation, before the curing treatment, the slurry is first cast into shape, covered with a plastic wrap, and allowed to stand for 18-30 hours in an environment of 18-22° C. and relative humidity ≥90% before the curing treatment is performed.

[0058] Preferably, the curing treatment is carried out in a constant temperature and humidity curing box.

[0059] As mentioned above, the third aspect of the present invention provides a chemically excited silicon-aluminum material prepared by the method described in the second aspect.

[0060] As mentioned above, the fourth aspect of the present invention provides the application of the chemically excited silicon-aluminum material described in the third aspect in the field of building materials.

[0061] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available or homemade.

[0062] Potassium silicate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., brand number P850160.

[0063] Slag: The content of silicon dioxide is 32.09wt%, the content of aluminum oxide is 16.55wt%, and the content of calcium oxide is 37.65wt%, which is purchased from Jiyuan Guotai Micro Powder Technology Co., Ltd.

[0064] Metakaolin: the content of silicon dioxide is 47.19wt%, the content of aluminum oxide is 49.11wt%, and the content of iron oxide is 0.79wt%, which is purchased from Inner Mongolia Chaoneng New Materials Co., Ltd.

[0065] Silica fume: SiO2 content is 97.42wt%, average particle size is 7.73μm, specific surface area is 1.80×10 5 m 2 / g, purchased from Shanghai Tiankai Building Materials Technology Co., Ltd., brand 970 silicon powder.

[0066] Carbon Black:

[0067] Carbon black I: Specific surface area is 420m 2 / g, with an average particle size of 23-28nm, purchased from Suqian Nakaite New Material Technology Co., Ltd., with the brand name Super-P.

[0068] Carbon black DI: specific surface area is 120-130m 2 / g, with an average particle size of 30-45nm, purchased from Jiangsu Pioneer Nanomaterials Co., Ltd., with the brand name XFI15.

[0069] Dispersant: Polyvinyl pyrrolidone, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., brand number P816205.

[0070] Defoaming agent: tributyl phosphate, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., brand number T818517.

[0071] The following preparation examples and comparative preparation examples are used to illustrate the preparation of potassium-based activators.

[0072] Preparation Example 1

[0073] Potassium silicate, potassium hydroxide and water are mixed to obtain a potassium-based activator, which is named chemical activator I;

[0074] The specific formula is shown in Table 1.

[0075] Preparation Example 2

[0076] This preparation example is carried out by a method similar to that of Preparation Example 1, except that the formula is different from that in Preparation Example 1.

[0077] A potassium-based activator was prepared and named as chemical activator II. The specific formula is shown in Table 1.

[0078] Comparative Preparation Example 1

[0079] This preparation example is carried out by a method similar to that of Preparation Example 1, except that the formula is different from that in Preparation Example 1.

[0080] A potassium-based activator was prepared and named as chemical activator DI. The specific formula is shown in Table 1.

[0081] Table 1

[0082] Preparation Example 1 Preparation Example 2 Comparative Preparation Example 1 Potassium silicate / g 3.39 3.95 4.52 Potassium hydroxide / g 5.85 5.63 5.42 Deionized water / g 35.71 34.66 33.61 Modulus of potassium-based activators 0.6 0.7 0.8 Content of alkali metal oxide of potassium-based activator / wt% 3.39 3.39 3.39 Solid content of potassium-based activator / wt% 20.56 21.65 22.82 Nomenclature of potassium-based activators Chemical activator I Chemical Activator II Chemical activator DI

[0083] Example 1

[0084] This example is used to illustrate the preparation of chemically excited silicon-aluminum materials according to the formula and process parameters shown in Table 2 and the following steps:

[0085] (1) mixing carbon black, an auxiliary agent (dispersant, defoamer) and a chemical stimulant by stirring to obtain a mixed solution I;

[0086] (2) subjecting the mixed solution I and the mixed material containing the basic components to a second stirring mixing to obtain a slurry;

[0087] (3) Casting the slurry into a mold, covering it with a plastic wrap, leaving it to stand in an environment of 20° C. for 24 hours, and then curing it in a constant temperature and humidity curing box to obtain the chemically excited silicon-aluminum material.

[0088] Example 2

[0089] This example is carried out in a similar manner to that of Example 1, except that the formula is different from that in Example 1.

[0090] A chemically excited silicon-aluminum material was prepared, and the specific formula is shown in Table 2.

[0091] Example 3

[0092] This embodiment is carried out in a similar manner to that of Embodiment 1, except that the amount of carbon black is adjusted to 0.5 g, the amount of dispersant is adjusted to 0.5 g, the amount of defoaming agent is adjusted to 0.25 g, and the rest is the same as that of Embodiment 1, to prepare a chemically excited silicon-aluminum material.

[0093] Comparative Example 1

[0094] This comparative example was carried out in a similar manner to Example 1, except that the formula was different from that in Example 1.

[0095] A chemically excited silicon-aluminum material was prepared, and the specific formula is shown in Table 2.

[0096] Comparative Example 2

[0097] This comparative example was carried out in a similar manner to Example 1, except that the formula was different from that in Example 1.

[0098] A chemically excited silicon-aluminum material was prepared, and the specific formula is shown in Table 2.

[0099] Comparative Example 3

[0100] This embodiment is carried out in a similar manner to that of Embodiment 1, except that an equal weight of chemical stimulant DI is used to replace the chemical stimulant I in Embodiment 1, and the rest is the same as that of Embodiment 1, to prepare a chemically excited silicon-aluminum material.

[0101] Comparative Example 4

[0102] This comparative example is carried out in a similar manner to Example 1, except that carbon black DI is used to replace carbon black I in Example 1, and the rest is the same as Example 1 to prepare a chemically excited silicon-aluminum material.

[0103] Comparative Example 5

[0104] This comparative example is carried out in a similar manner to Example 1, except that the amount of carbon black I is adjusted to 10 g, the amount of dispersant is adjusted to 10 g, the amount of defoamer is adjusted to 5 g, and the rest is the same as Example 1, to prepare a chemically excited silicon-aluminum material.

[0105] Table 2

[0106] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Basic components Slag / g 80.0 80.0 60.0 80.0 Metakaolin / g 15.0 5.0 30.0 20.0 Silica fume / g 5.0 15.0 10.0 0 Carbon black / g type Carbon Black I Same as Example 1 Same as Example 1 Same as Example 1 Dosage / g 6 4 Same as Example 1 Same as Example 1 Chemical activators type Chemical activator I Chemical Activator II Same as Example 1 Same as Example 1 Dosage / g 44.95 44.24 Same as Example 1 Same as Example 1 Additives Dispersant / g 6 4 Same as Example 1 Same as Example 1 Defoaming agent / g 3 2 Same as Example 1 Same as Example 1 First stir to mix Speed / rpm 800 Same as Example 1 Same as Example 1 Same as Example 1 Time / min 40 Same as Example 1 Same as Example 1 Same as Example 1 Second stirring mix Speed / rpm 145 Same as Example 1 Same as Example 1 Same as Example 1 Time / min 2 Same as Example 1 Same as Example 1 Same as Example 1 Maintenance Temperature / ℃ 20 Same as Example 1 Same as Example 1 Same as Example 1 humidity / % 90 Same as Example 1 Same as Example 1 Same as Example 1

[0107] Test Case

[0108] (1) The fluidity of the slurry obtained in step (2) of the above example was tested using the method specified in GB / T 8077-2000;

[0109] (2) The solidification time (including initial setting time and final setting time) of the chemically excited silicon-aluminum material prepared in the above example was tested using the method specified in GB / T 1346-2011;

[0110] (3) The compressive strength of the chemically excited silicon-aluminum material prepared in the above example was tested by the method specified in GB / T 17671-2021 (compressive strength after 28 days of curing);

[0111] (4) The AC resistivity of the chemically excited silicon-aluminum material prepared in the above example was tested according to the method in https: / / doi.org / 10.1016 / j.jobe.2022.105022 to evaluate the conductive properties of the chemically excited silicon-aluminum material (AC resistivity after 28 days of curing);

[0112] The results of the above performance tests are shown in Table 3.

[0113] Table 3

[0114]

[0115] It can be seen from the above results that the slurry prepared by the chemically excited silicon-aluminum material composition provided by the present invention has good fluidity, and the obtained chemically excited silicon-aluminum material has a suitable setting time and can still maintain excellent compressive strength and conductivity after 28 days.

[0116] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A chemically excited silicon-aluminum material composition, characterized in that: The composition contains a main agent and an auxiliary agent; the main agent includes a base component, carbon black and a chemical activator; Relative to 100 parts by weight of the base component, the content of the carbon black is 0.5-6 parts by weight, and the content of the chemical stimulant is 40-50 parts by weight; Based on the total weight of the basic component, the basic component contains 60-80wt% of slag, 5-20wt% of metakaolin and 5-20wt% of silica fume; The specific surface area of ​​the carbon black is 405-435m 2 / g, average particle size is 20-40nm; The modulus of the chemical activator is less than 0.8, and the content of alkali metal oxide in the chemical activator is 3-4wt%, and the solid content is 14-25wt%.

2. The composition according to claim 1, characterized in that The modulus of the chemical activator is 0.6-0.

7.

3. The composition according to claim 1 or 2, characterized in that The content of the carbon black is 4-6 parts by weight relative to 100 parts by weight of the base component; And / or, based on the total weight of the base component, the base component contains 70-80wt% of slag, 5-15wt% of metakaolin and 5-15wt% of silica fume.

4. The composition according to any one of claims 1 to 3, characterized in that The content of SiO2 in the silica ash is ≮96wt%; And / or, the average particle size of the silica fume is 0.35-21.5 μm, and the specific surface area is 1.75×10 5 -1.80×10 5 m 2 / g.

5. The composition according to any one of claims 1 to 4, characterized in that The slag contains 30-45 wt% silicon dioxide, 10-20 wt% aluminum oxide and 35-50 wt% calcium oxide; And / or, the content of silicon dioxide in the metakaolin is 45-60wt%, the content of aluminum oxide is 35-50wt%, and the content of iron oxide is less than 2wt%.

6. The composition according to any one of claims 1 to 5, characterized in that The auxiliary agents include dispersants and defoamers; Relative to 100 parts by weight of the base component, the content of the dispersant is 0.01-6 parts by weight, and the content of the defoaming agent is 0.005-3 parts by weight.

7. A method for preparing a chemically excited silicon-aluminum material, characterized in that: The method is carried out using the components in the chemically excited silicon-aluminum material composition according to any one of claims 1 to 6, and comprises: (1) Stirring and mixing the components in the main agent and the components in the auxiliary agent to obtain a slurry; (2) The slurry is subjected to a curing treatment to obtain the chemically excited silicon-aluminum material.

8. The method according to claim 7, characterized in that In step (1), the step of stirring and mixing the components in the main agent and the components in the auxiliary agent comprises: S1: mixing carbon black, an additive and a chemical activator by stirring to obtain a mixed solution I; S2: The mixed solution I and the mixed material containing the basic components are subjected to a second stirring and mixing process to obtain a slurry.

9. The chemically excited silicon-aluminum material prepared by the method according to claim 7 or 8.

10. Use of the chemically excited silicon-aluminum material according to claim 9 in the field of building materials.

Citation Information

Patent Citations

  • Conductive geopolymer preparation method

    CN105218004A

  • Geopolymer composition, geopolymer material and preparation method of geopolymer material

    CN104098281A

  • Preparation method of alkali-activated high-silica bauxite ore based gel material with adjustable electric conductivity

    CN105731895A

  • Graphene oxide-nano mineral enhanced geopolymer material and preparation method thereof

    CN110981298A

  • Slag-based alkali-activated cementing material as well as preparation method and application thereof

    CN112408819A